2020
DOI: 10.1002/ffj.3572
|View full text |Cite
|
Sign up to set email alerts
|

α‐glucosidase, α‐amylase inhibitory potential and antioxidant activity of fragrant black rice (Thai coloured rice)

Abstract: Diabetes mellitus is the most serious metabolic disorder in the world. 1 A recent report from the World Health Organization (WHO) showed that more than 422 million people worldwide have diabetes, especially in low-and middle-income countries. Diabetes mellitus can be divided into two types: insulin-dependent (type 1 diabetes mellitus) and non-insulin-dependent (type 2 diabetes mellitus). The common patients with diabetes are type 2 patients. Type 2 diabetes mellitus is caused by high blood glucose level whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The free‐radical scavenging capacity of plant extract and rice extract has commonly been analysed using DPPH• and ABTS•+ assays (Chaiyasut et al ., 2017; Bari et al ., 2019; Zafar et al ., 2019; Sansenya & Nanok, 2020). The free‐radical scavenging capacity of plant extract is closely related to the phenolic content and flavonoid content (Amri & Hossain, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The free‐radical scavenging capacity of plant extract and rice extract has commonly been analysed using DPPH• and ABTS•+ assays (Chaiyasut et al ., 2017; Bari et al ., 2019; Zafar et al ., 2019; Sansenya & Nanok, 2020). The free‐radical scavenging capacity of plant extract is closely related to the phenolic content and flavonoid content (Amri & Hossain, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition potential of rice extract against α‐glucosidase, α‐amylase, and tyrosinase was determined by the modified method of Sansenya & Nanok (2020). AB and KA were used as the standard inhibitors for α‐glucosidase and α‐amylase activity and tyrosinase activity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of phytochemical components, including flavonoids, terpenoid, and reducing sugar, were determined following the method of Sansenya and Nanok (2020) , with modifications. First, the crude methanol extract was dissolved in deionized water to produce 1 mg/mL solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds have many biological activities, for instance, antioxidant [40,41] and anti-inflammatory properties [42]. Several epidemiological studies suggested that high dietary consumption of polyphenols is associated with decreased risk of a range of diseases including antidiabetic [43,44], cardiovascular disease (CVD) [45], and neurodegenerative diseases [46].…”
Section: Health Benefit Potentials Of Pigmented Ricementioning
confidence: 99%
“…The potential inhibition against α-amylase activity in black rice samples were higher than those in red and purple rice samples, respectively [13]. In addition, the percentage inhibition on α-glucosidase and α-amylase of fragrant black rice fractions had higher potential than acarbose, a synthetic antidiabetic drug [48]. However, variation in the structure of anthocyanins makes it difficult to determine their effects on Type II diabetes.…”
Section: Antidiabetic Activitymentioning
confidence: 99%